Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:1. Risks of Misuse of Electronic Games on Children and Their Remedies  from the Perspective of Islamic EducationMs. Rasha Ahmad Baniismail, Dr. Ayesh Ali Lababneh2. The Sustainable US Strategy for Leading the International SystemAsst-Prof. Shadi Sameer Ewadia3. Spatial Analysis of Land use in Qibah County from 1993 to 2023Mr. Ahmed Ali Mujalli, Co-Prof. Abdulrahman Suleiman Al-Nosaiyan4. The Impact of Digital Advertising on Consumer Behavior: An Applied Study on Social Media UsersDr. Sara Saad Al-Dawsari ,Dr. Sadiq Ali Mubarak Al-Shuwaikhat5. Newlyweds' Perspectives in Jeddah Towards a Prevention Program Based on the Concept of Differentiation of SelfMs. Musleha Ali Alshomrani, Dr. Yosra Mohammed Bugis6. Exploring the Symbolism of Nature in the Works of Thomas Hardy: An Eco-critical perspectiveDr. Areej Saad Almutairi
Keywords: Journal of Human and Social Sciences